Silver nanoparticles in X-ray biomedical applications. (January 2017) - Mattea, Facundo; Vedelago, José; Malano, Francisco; Gomez, Cesar; Strumia, Miriam C.; Valente, Mauro
Abstract: The fluorescence of silver nanoparticles or ions can be used for detection and dose enhancement purposes in X-ray irradiation applications. This study is focused on the full integration of the chemical synthesis of silver nanoparticles suitable for dosimetric and radiological purposes with characteristics that can be exploited in radiotherapy and radiodiagnostic. A narrow size distribution and a compatible stabilizing agent is often desired in order to obtain homogeneous behaviors in nanoparticle suspension. With the method proposed in this study, nanoparticles ranging from 5 to 20 nm were obtained. The fluorescence of aqueous suspensions of silver nanoparticles has been measured experimentally and simulated with the Monte Carlo PENELOPE code for different silver concentrations and geometrical configurations. Finally, the feasibility of using these nanoparticles for the elaboration of Fricke gel dosimeters has been tested obtaining a dose enhancement when compared with the same material irradiated below the silver K-edge. Highlights: A method to compare NP's fluorescence in simulations and experiments was developed. Silver nanoparticles suitable for typical dosimetry systems were synthesized. Concentration and depth of a Ag doped volume was measured with X-ray fluorescence. A feasibility test of Ag NPs in Fricke gel dosimetry was performed. Good agreement between Monte Carlo simulations and experiments was obtained.